A prática de atividades físicas e esportivas na adolescência como estratégia no combate à obesidade - RIBEIRO, Udson Mychel do Nascimento (2020)
For a healthy life, it is necessary to have good eating habits and to practice physical exercises or any activity that has as main objective the corporal movement; this applies to every individual. However, when you are in the transition phase, that is, when you are entering adolescence, the individual undergoes transformations that will change the body and, consequently, the mind. This paper proposes a discussion about obesity among adolescents and poor eating habits that are part of the lives of the vast majority of Brazilians with the purpose of encouraging them to practice physical and sports activities and to contemplate the benefits that it will provide them. For data collection, besides observation, a questionnaire was applied with a group of 25 adolescents. Given this, the methodology used was very important considering the reality of this public usually influenced by social media and fast foods, foods that often leave them more prone to physical inactivity and obesity. As a result, it was possible to verify that the eating habits and the practice of physical activities by adolescents interviewed are cultivated, thus indicating a concern with their own health and their quality of life.